2019
DOI: 10.1115/1.4042256
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Flow Through a Ducted Elbow and Plugged Tee Geometry: An Experimental and Numerical Study

Abstract: An experimental and computational comparison of the turbulent flow field for a sharp 90 deg elbow and plugged tee junction is presented. These are commonly used industrial geometries with the tee often retrofitted by plugging the straight exit to create an elbow. Mean and fluctuating velocities along the midplane were measured via two-dimensional (2D) particle image velocimetry (PIV), and the results were compared with the predictions of Reynolds-averaged Navier–Stokes (RANS) simulations for Reynolds numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In industrial facilities, all the fluids are distributed by hydraulic circuits, that have different components, such as pipes [65,83], sudden or abrupt contractions and expansions [55,110], elbows [111,112], flow meters and controllers [113,114], static mixers [115,116], tees, bends and pumps. Due to surface colonization by microorganisms, biofouling development in these systems is inevitable with more persistence in regions characterized by low hydrodynamics.…”
Section: Fluid Distribution Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In industrial facilities, all the fluids are distributed by hydraulic circuits, that have different components, such as pipes [65,83], sudden or abrupt contractions and expansions [55,110], elbows [111,112], flow meters and controllers [113,114], static mixers [115,116], tees, bends and pumps. Due to surface colonization by microorganisms, biofouling development in these systems is inevitable with more persistence in regions characterized by low hydrodynamics.…”
Section: Fluid Distribution Networkmentioning
confidence: 99%
“…In fact, Simunic et al [44] verified that in dead-end zones, fouling was not affected by fluid flushing (high turbulence from high fluid velocity) that was typical for the main pipe. Several studies identified critical areas for fouling formation such as the regions closed to corners and baffles [59,75,104] and header section [102] in HE, regions closed to expansions/contractions [110,120], angles [128,134], elbows [112,133], and valves [12,114] in distribution networks, and regions closed to corners in the bottom [154], and baffles in the tank wall [165] in STRs. In addition of being prone for fouling phenomena, dead-end zones affect CIP efficacy, compromising the process and product quality, and increase operating and maintenance costs [12].…”
Section: Hydrodynamics On (Bio)fouling Prevention and Controlmentioning
confidence: 99%
“…The MCCS structure is a combined manifold consisting of several channel pipes, a clustered pipe and a main pipe. According to reference [7], a pugged tee junction creates less pressure loss than a sharp 90 degree elbow in a turbulent flow field. Therefore, the form of the channel pipe and clustered pipe is a T-connection.…”
Section: Geometries' Structuresmentioning
confidence: 99%
“…The MCCS structure is composed of pipes and T-shaped tees. Andrew M. Bluestein presents the turbulent flow field for a sharp 90 degree elbow and a plugged, T-shaped junction by experiment and computation, and the conclusion shows that a pugged T-shaped structure creates less pressure loss than a sharp elbow [7]. It is mainly reasoned that the MCCS structure consists of a T-shaped rather than elbow-shaped.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation